Heterogeneous Co3O4 catalyst for selective oxidation of aqueous veratryl alcohol using molecular oxygen - Mate, Vivek R.; Shirai, Masayuki; Rode, Chandrashekhar V. (Catalysis Communications, 2013)
Nano-structured, spinel Co3O4 catalyst was developed for the aqueous phase oxidation of veratryl alcohol, which showed the highest conversion of 85% with 96% selectivity to veratryl aldehyde. The co-existence of Co3+ and Co2+ species in the octahedral and tetrahedral positions respectively, was confirmed by XPS, cyclic voltammogram, TPR and TPO characterization. The rod-like morphology of Co3O4 catalyst was confirmed by HRTEM. The effects of various reaction parameters namely, catalyst concentration, temperature and partial oxygen pressure on conversion and selectivity patterns were also studied for the oxidation of veratryl alcohol. This catalyst also showed an excellent stability as evidenced by successful reusability for three times. (C) 2012 Published by Elsevier B.V.
Keywords: Co3O4; Cyclic voltammogram; Liquid phase oxidation; Molecular oxygen; Veratryl alcohol; XPS

Hydrogenolysis of benzofuran using aqueous ethanol solution over graphite-supported platinum catalyst - Hiraishi, Yushi; Minakawa, Naohiro; Taniguchi, Kenkichi; Nagasawa, Yoshiyuki; Nanao, Hidetaka; Rode, V, Chandrashekhar; Sato, Osamu; Yamaguchi, Aritomo; Shirai, Masayuki (Journal of the Indian Chemical Society, 2021)
Graphite-supported platinum catalysts (Pt/G) were highly active for the hydrogenolysis of benzofuran to o-ethylphenol in aqueous ethanol solution at 523 K without using any external hydrogen gas. The hydrogenolysis activities and selectivity to o-ethylphenol in ethanol solution over Pt/G were higher than those with a conventional method using externally supplied hydrogen gas. Both water and ethanol were indispensable for the hydrogenolysis in aqueous ethanol solution at 523 K.
Keywords: Biomass conversion; Graphite support; Hydrogenolysis; platinum catalysts